The Effects of Domestic Plastic Waste on Concrete Properties: Sustainable Replacement of Aggregates - Ahmad, Siti Hamizah; Md Amin, Noor Dina; Ali, Noorwirdawati (Recent Trends in Civil Engineering and Built Environment, 2025)
Malaysia is the largest contributor to plastic waste disposal in Southeast Asia. It is due to the fact that, with the existing way of life, users choose to use plastic in their daily lives without knowing the impact of its use. Plastic is a material that does not easily break down and dissolve naturally. It requires a long period of time to break down and decompose. So, the concept of recycling is one way to save nature and this concept can also be practiced in the construction sector such as construction materials. Therefore, this study identifies the appropriate ratio of cement, water, plastic replacement, and aggregate in the concrete. In addition, this study determines the effect of domestic replacement of waste plastic on concrete properties. The third objective is to compare the concretes with admixtures without plastic with admixtures with plastic replacement along with fine aggregate and coarse aggregate. This study focuses on the use of polyethylene terephthalate (PET) plastic with 10% and 20% replacement levels in both fine aggregate and coarse aggregate. The appropriate ratio for the concrete aggregate is identified by using the DoE (Department of Environment) method. Several tests were conducted to test the workability of the concrete, namely slump test, density for hardened concrete, water absorption and compressive strength. Based on the results obtained, the density of coarse aggregate plastic concretes (DP10C, DP20C) is higher than that of fine aggregate plastic concretes (DP10F, DP20F). Meanwhile, the water absorption rate for coarse aggregate plastic concretes (DP10C) is more lower than fine aggregate (DP10F) for both 7 days and 28 days curing. As for compressive strength test, the replacement of concrete with coarse aggregate (DP20C) is more higher than fine aggregate (DP20F). The replacement for fine aggregate has a limit up to 10%, if exceeding that percentage, the strength of concrete will decrease drastically. In conclusion, the replacement of plastic in concrete has a good effect on the environment and the concept of sustainable concrete is achieved.